Negative and Positive Freedom: The Case of Turkey - Özçelik, Tacettin Gökhan (Review of European and Comparative Law, 2024)
The meaning of the concept of freedom has constantly changed in history. In Ancient Greece, freedom referred to making a choice and doing something willingly; Hannah Arendt conceptualized it as a necessary discovery made by people in historical periods when the conditions for manifesting the idea of searching the same concept within oneself as an action were insufficient. Today, the concept of freedom has evolved into a dual meaning as negative and positive, shaped by the expressions of Isaiah Berlin. In this sense, the freedoms that we call classical freedoms, which the individual acquires because of being human, without considering the differences in religion, language, gender, and race, are evaluated in the context of negative freedoms. The basis of this understanding is the absence of pressure and coercion from the environment in which the individual lives rather than the creation of surplus value in the individual by external influence. However, with the deterioration of the freedom concept, the gains included in negative freedom have become a problem that the state needs to solve. The need for state intervention in creating a positive effect on the individual has emerged. The concept of positive freedom that emerged in this sense reveals itself in a structure that requires more than the intervention of others; it requires that individuals have control over their selves and that they have an active role in this dominance. Proponents of positive freedom argue that freedom means the individual dominates their own passions, desires, and all obstacles to self-realization. In order to achieve this, the state must firmly stand by the individual regarding collective freedoms. In this context, since the discussions on the concept of rights and freedoms in Turkey spread to negative and positive areas of freedom, this paper aims to show that presenting the concept with a single definition of freedom would be challenging. The re-reading has shown that the rights and freedoms in Turkey are derived from the concept of both positive and negative individual rights. However, it has been observed that the framers of the Constitution limited the fundamental rights and freedoms based on the idea that there should be a limit to the individual’s rights and covered it in the necessary sections in the Constitution to ensure that the fundamental rights and freedoms could not be abused.